The Gnoseological Aspect of the Primitive World Outlook Reconstruction - Vaitkutė, Bronislava (Problemos, 1970)
The religious aspect of the investigation of the spiritual life in the primitive society is nearly the only aspect in our scientific literature. The paper deals with the problem or nature or the primitive world outlook being of complicated and contradictory character, what stipulates the possibility of considering it from various aspects, not allowing although to characterize it unequivocally and to absolutely dissolve it in religion. On the basis of V. I. Lenin’s heritage the author draws a conclusion that scientific investigations must distinguish in the primitive consciousness both religious-mystical and rationally-cognitive tendencies which are formed under the influence or various requirements of society. The important prerequisite for scientific investigation of the primitive world outlook is the strict discrimination of separate aspects of its investigation. The discrimination of religious and gnoseological aspects of analysis is of particular importance. In the gnoseological aspect the problem of the primitive world outlook appears as the problem of pre-history or scientific cognition.